Examining the Link Between Information Technology Utilization, Work-Family Conflict, Commitment and Employee Performance - Maulidina, Akmal; Hidayah, Zainur; Maharani, Anita (LPPM Universitas Terbuka, 2021)
This study analyzes the link between information technology utilization, work-family conflict, commitment, and employee performance. As this research targeting explorations, the total sample receive is 104 data, out of 210 samples targeted. The target of respondents is employees work in institution implementing work from home. The collected research data is still acceptable because the rate-of-returned questionnaire is> 80%. The research hypothesis testing carries out using the Structural Equation Model (SEM) approach based on Partial Least Square (PLS). From the results, employee’s utilization of information technology does not have a significant effect on commitment. However, this research contributes to the fact that employee performance influences the quality of work-family conflict and commitment.